Analisis Sentimen Terhadap Aplikasi Tiktok Dari Ulasan Pada Google Playstore Menggunakan Metode Naïve Bayes - Nizar Fawwazun Hilmi; Faldy Irwiensyah (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
In this research, we use reviews from the Google Play Store platform to conduct sentiment analysis on the TikTok application. Reviews can be categorized into positive, negative, or neutral sentiment groups using a Naïve Bayes approach. The distribution of user sentiment towards TikTok is displayed in the sentiment analysis results. Exposing model performance allows you to observe the level of understanding, accuracy, and precision of emotion classification. Our findings provide marketers and app developers with in-depth information about how users view TikTok. The accuracy level, precision level, and recall level of the Naive Bayes algorithm used for sentiment analysis for evaluating users of the TikTok application on the Google Play Store are 83.66%, 82.97%, and 91.97%, respectively. From the accuracy figures, it is clear that the Naive Bayes method provides reliable results so it is suitable for use in data categorization.